DOMINANT ATTRIBUTE OF MANGO INDOOR FRAGRANCE - Yosini Deliana; Sri Fatimah; Mohamad Djali (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Mango produced from Cirebon, Indramayu dan Sumedang  have different qualities . Those types of mango is  already has its own market segment. The on farm problem is mango producers do not know exactly how consumer preferences for mango from Cirebon, Indramayu and Sumedang. When the harvest time , over supply and mango price getting decrease. The idea to solve this problem is to process  mango over supply become mango indoor fragrance. Variables that distinguish consumer preference are easy to find, aroma, colour, duration, freshness, water content, expire date, purpose, information and additional esens. The purpose of this study to analysis respondent’s characteristics,  dominant attribute of mango indoor fragrance which are the least dominant attribute of these product.